Implementasi Program Kampus Mengajar dalam Meningkatkan Literasi pada Siswa Kelas III SD Inpres Kajenjeng di Era Pandemic Covid-19 - Sucianti Basri; Supriadi Supriadi; Nur Syam; Nur Afni; Nurhayati Selvi (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The Teaching Campus Program is one form of the implementation of the Merdeka-Belajar-Kampus-Merdeka (MBKM) in the form of teaching activities, technology adaptation, and administration by empowering students to assist the learning process in elementary schools in various villages/cities. One of them is in SD Inpres Kajenjeng which is located on Jalan RPH. Kajenjeng number 554, Tamangapa sub-district, Manggala sub-district, Makassar City. The aim of the Teaching Campus Program is to provide solutions for schools affected by the pandemic, especially at the elementary level with the 3T predicate (Front, Disadvantaged, Remote) and provide opportunities for them to learn and develop themselves. And by empowering students who live around the school area to help schools provide optimal educational services to all students at the elementary level in limited and critical conditions during the pandemic as well as assisting in the implementation of learning that focuses on learning literacy and numeracy both offline and online. This program has a positive impact on students such as increasing motivation and interest in learning, improving integrated literacy and numeracy skills and the effectiveness of the learning process.